Analysis Young Driver Behavior in “Z” Generation - Yogi Arisandi; Khusnul Khotimah (Journal of Social Science, 2020)
The magnitude of the cause of the accident due to driver error causes the need to do an analysis related to the characteristics of the driver and the factors that most influence the cause of the accident and then the road. At this time the young driver is in generation Z who has an age between 16-21 years. Then an analysis of the characteristics of the causes of traffic accidents, especially in the "Z" generation of drivers by using the driver simulator "Teknosim" and the results of the analysis of observations through crosstab models and chi square test to the influential variable. Obtained the characteristics of the generation driver "Z" in low traffic tend to move lane under the right conditions, brake suddenly with very minimal dexterity, this causes collisions with other vehicles with a very short reaction time without agility of 0.012 minutes, and not yet can improve how to drive and can not prevent wasteful consumption of fuel even in traffic that is not dense with Asymp.Sig values. (2-sided) in the amount of 0.010 - 0.014. In heavy traffic conditions, the "Z" Generation driver has the characteristic of tapping the horn and tends to brake suddenly with a very small braking distance or too close to the vehicle in front of him and very minimal dexterity with the Asymp.Sig value. (2-sided) in the amount of 0.014 - 0.017.